Rare earth modified V-Cr-Mn iron-based wear-resistant alloy material and preparation method thereof

By modifying the V-Cr-Mn iron-based wear-resistant alloy material with a specific element composition and process flow, the existing V-Cr-Mn iron-based wear-resistant alloy has high vanadium content and complex process problems, achieving the effects of cost reduction, process simplification and performance improvement.

CN116516256BActive Publication Date: 2025-04-15INNER MONGOLIA HUANTOU ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310504091.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-06
Publication Date
2025-04-15
Estimated Expiration
2043-05-06

AI Technical Summary

Technical Problem

The existing V-Cr-Mn iron-based wear-resistant alloys have problems with high vanadium content and complex process flow, which limits their use.

Method used

By modifying the V-Cr-Mn iron-based wear-resistant alloy material with a specific element composition and process flow, including smelting and insulation at a temperature of 1500-1550°C, and using the rare earth element cerium (Ce) to improve the morphology of vanadium carbide (VC) and the overall performance of the material.

Benefits of technology

It reduces the refining cost of materials, simplifies the process flow, and improves the wear resistance and hardness of materials, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116516256B_ABST
    Figure CN116516256B_ABST
Patent Text Reader

Abstract

The present invention relates to a rare earth modified V-Cr-Mn iron-based wear-resistant alloy material and a preparation method thereof, comprising 2.0% to 3.0% carbon, 0.8% to 1.6% silicon, 6.0% to 12.0% chromium, 4.0% to 8.0% manganese, 5.0 to 8.0% vanadium, 0.1% to 0.3% rare earth element cerium, and the rest being iron Fe. The ratio of the raw materials is set according to the above-mentioned component contents and the composition of the raw materials, and the charge is configured. After the charge is smelted at a temperature of 1500-1550° C. in an induction furnace for 10 to 30 minutes, it is kept warm for 30-50 minutes under the same temperature conditions. Thereafter, the molten iron at a temperature of 1500-1550° C. is poured into a preheating ladle, the melt is covered with dry exothermic powder, and slag is removed while maintaining the temperature. Before being discharged from the furnace, it is finally deoxidized with aluminum wire and poured into a resin sand mold for casting and forming to obtain a rare earth modified V-Cr-Mn iron-based wear-resistant alloy material. The smelting temperature is reduced while reducing the amount of vanadium used.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a V-Cr-Mn iron-based wear-resistant alloy material, in particular to a rare earth modified V-Cr-Mn iron-based wear-resistant alloy material and a preparation method thereof. Background Art

[0002] The materials of some key components in mechanical equipment need to have high hardness, high wear resistance and high toughness at the same time, such as the liner and grinding balls in the ball mill. The ball mill is used to grind various ores and other materials. When grinding ores and other materials, the liner and grinding balls will be subject to frequent non-directional impacts and repeated grinding with the materials. They are usually made of wear-resistant alloy materials such as high-hardness high-chromium (Cr) cast iron or high-toughness high-manganese (Mn) steel to prevent rapid wear by powdered materials. However, the disadvantages of high-chromium cast iron and high-manganese steel are that they have low wear resistance, short service life of the liner and grinding balls, and need to be replaced frequently, and high cost of use.

[0003] As a wear-resistant alloy, V-Cr-Mn iron-based wear-resistant alloy has better performance than high-chromium cast iron and high-manganese steel. The performance of V-Cr-Mn iron-based wear-resistant alloy depends on the vanadium content and structure, among which the main role is played by the aggregated vanadium carbide (VC) particles. To produce ideal vanadium carbide particles, the vanadium content (percentage) must reach 9% or even more than 12%, and it must be smelted at a temperature above 1700°C and subsequently heat treated. Not only is the smelting temperature high and the process complicated, but it also requires a large amount of expensive vanadium, which limits the use of V-Cr-Mn iron-based wear-resistant alloy. Summary of the invention

[0004] The purpose of the invention is to solve the problems of high vanadium content and complicated process flow in the existing V-Cr-Mn iron-based wear-resistant alloy.

[0005] The first technical solution is that the rare earth modified V-Cr-Mn iron-based wear-resistant alloy material is composed of the following components in mass percentage:

[0006] Carbon (C): 2.0% to 3.0%, Silicon (Si): 0.8% to 1.6%, Chromium (Cr): 6.0% to 12.0%, Manganese (Mn): 4.0% to 8.0%, Vanadium (V): 5.0% to 8.0%, Rare earth element Cerium (Ce): 0.1% to 0.3%, the rest is Iron (Fe),

[0007] The rare earth modified V-Cr-Mn iron-based wear-resistant alloy material is made of raw materials meeting the above components, smelted at a specified smelting temperature of 1500-1550°C and a specified smelting time (T1), and then kept warm for a specified holding time (T2) to obtain molten iron pouring at 1500-1550°C.

[0008] Preferably, it is composed of the following components in percentage by mass:

[0009] Carbon (C): 2.0%~2.3%, Silicon (Si): 0.80%~1.0%, Chromium (Cr): 6.0%~8.0%, Manganese (Mn): 4.0%~5.0%, Vanadium (V): 5.0~6.0%, Rare earth element Cerium (Ce): 0.1%~0.2%, and the rest is Iron (Fe).

[0010] Preferably, the melting time (T1) is set to 30-50 min, and the holding time (T2) is set to 10-30 min.

[0011] Preferably, the material comprises scrap steel, pig iron, ferrovanadium, ferrochrome, ferromanganese and / or a recarburizer.

[0012] The second technical solution is a method for preparing a rare earth modified V-Cr-Mn iron-based wear-resistant alloy material, wherein the wear-resistant alloy is composed of the following components in percentage by mass:

[0013] Carbon (C): 2.0% to 3.0%, Silicon (Si): 0.8% to 1.6%, Chromium (Cr): 6.0% to 12.0%, Manganese (Mn): 4.0% to 8.0%, Vanadium (V): 5.0% to 8.0%, Rare earth element Cerium (Ce): 0.1% to 0.3%, the rest is Iron (Fe),

[0014] The preparation method comprises the following steps:

[0015] Batching step (S1): Determine the element content of various materials, calculate the mass of various materials for configuring the wear-resistant alloy element components according to the determination results, weigh the materials accordingly, and then weigh a certain amount of rare earth inoculant, and use the weighed materials and rare earth inoculant as furnace charge.

[0016] Smelting step (S2): putting the prepared charge into an electric furnace for smelting at a smelting temperature of 1500-1550°C and a specified smelting time (T1), and then keeping the temperature for a specified holding time (T2) to obtain molten iron at 1500-1550°C.

[0017] The step of taking out the furnace and casting (S3): taking out the molten iron at 1500-1550°C and pouring it into a preheating ladle as a melt, while maintaining the temperature of the melt and performing slag removal, and then pouring it into a mold for casting and forming, thereby producing a rare earth modified V-Cr-Mn iron-based wear-resistant alloy material.

[0018] Preferably, the wear-resistant alloy consists of the following components in percentage by mass:

[0019] Carbon (C): 2.0%~2.3%, Silicon (Si): 0.80%~1.0%, Chromium (Cr): 6.0%~8.0%, Manganese (Mn): 4.0%~5.0%, Vanadium (V): 5.0~6.0%, Rare earth element Cerium (Ce): 0.1%~0.2%, and the rest is Iron (Fe).

[0020] Preferably, the melting time (T1) is set to 30-50 min, and the holding time (T2) is set to 10-30 min.

[0021] Preferably, the material comprises scrap steel, pig iron, ferrovanadium, ferrochrome, ferromanganese and / or a recarburizer. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a step-by-step diagram of a method for preparing a rare earth modified V-Cr-Mn iron-based wear-resistant alloy material (wear-resistant alloy);

[0023] Figure 2 is a SEM / EDS analysis illustration of the wear-resistant alloy prepared in Example 1;

[0024] Figure 3 is an illustration of the metallographic analysis of the wear-resistant alloy prepared in Example 1;

[0025] Figure 4 is an illustration of the metallographic analysis of the V-Cr-Mn iron-based alloy prepared in Comparative Example 1;

[0026] Figure 5 is an illustration of the metallographic analysis of the V-Cr-Mn iron-based alloy prepared in Comparative Example 2;

[0027] Figure 6 is a comparative illustration of the hardness of the alloys in Example 1 and Comparative Example 2;

[0028] Figure 7 It is a comparative illustration of the alloy wear amount in Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0029] The specific implementation methods of the rare earth modified V-Cr-Mn iron-based wear-resistant alloy material (hereinafter referred to as wear-resistant alloy) of the present invention are described in detail below in conjunction with the accompanying drawings by listing three embodiments and two comparative examples. Example 1

[0030] Wear-resistant alloys are composed of the following elemental components in mass percentage:

[0031] Carbon C: 2.0%, Silicon Si: 0.80%, Chromium Cr: 6.0%, Manganese Mn: 4.0%, Vanadium V: 5.0%, Cerium Ce: 0.10%, and the rest is Iron Fe. Table 1 shows the elements and their corresponding components.

[0032] Table 1 Element composition of wear-resistant alloy in Example 1

[0033]

[0034] The preparation method of the rare earth modified V-Cr-Mn iron-based wear-resistant alloy material is described below.

[0035] Figure 1 The following is a step-by-step diagram of a method for preparing a rare earth modified V-Cr-Mn iron-based wear-resistant alloy material (wear-resistant alloy). The raw materials are scrap steel, pig iron, ferrochrome, ferromanganese, ferrovanadium, and ferrosilicon, and a rare earth inoculant containing cerium (hereinafter referred to as rare earth inoculant) is added for smelting.

[0036] like Figure 1 As shown, the method for preparing the above-mentioned wear-resistant alloy comprises the following steps:

[0037] Batching step S1: Batching is performed according to the element composition of the wear-resistant alloy and the components in the raw materials, and the usage of scrap steel, pig iron, ferrochrome, ferromanganese, ferrovanadium, ferrosilicon and rare earth inoculant is determined to configure the furnace charge.

[0038] First, the elemental composition of the raw materials is analyzed. In this embodiment, the element content of the scrap steel is carbon C: 0.20%, silicon Si: 0.40%, manganese Mn: 0.45%, vanadium V: 0%, chromium Cr: 0%, sulfur S: 0.01%, phosphorus P: 0.04%, and the rest is iron Fe; the element content of the pig iron is carbon C: 4.37%, silicon Si: 0.68%, manganese Mn: 0.12%, vanadium V: 0%, chromium Cr: 0%, sulfur S: 0.026%, phosphorus P: 0.05%, and the rest is iron Fe; the element content of ferrosilicon is carbon C: 0.15%, silicon Si: 72.1%, manganese Mn: 0%, vanadium V: 0%, chromium Cr: 0%, sulfur S: 0.016%, phosphorus P: 0.034%, and the rest is iron Fe; ferrosilicon is carbon C: 0.15%, silicon Si: 72.1%, manganese Mn: 0%, vanadium V: 0%, chromium Cr: 0%, sulfur S: 0.016%, phosphorus P: 0.034%, and the rest is iron Fe; ferrovanadium The element contents in it are carbon C: 0.53%, silicon Si: 0.61%, manganese Mn: 0.43%, vanadium V: 49.38%, chromium Cr: 0%, sulfur S: 0.032%, phosphorus P: 0.058%, and the rest is iron Fe; the element contents in ferrochrome are carbon C: 8%, silicon Si: 1.89%, manganese Mn: 0%, vanadium V: 0%, chromium Cr: 59.01%, sulfur S: 0.026%, phosphorus P: 0.144%, and the rest is iron Fe; the element contents in ferromanganese are carbon C: 6.5%, silicon Si: 0.8%, manganese Mn: 65.1%, vanadium V: 0%, chromium Cr: 0%, sulfur S: 0.02%, phosphorus P: 0.17%, and the rest is iron Fe (summarized in Table 2).

[0039] Table 2 Element composition of various raw materials

[0040]

[0041] According to the elemental composition of the wear-resistant alloy and the elemental composition of the raw materials, the ratio of the raw materials is set, and the refining of 10 kg (one furnace) of wear-resistant alloy is calculated. The furnace charge is determined to be 4.84 kg of scrap steel, 2.5 kg of pig iron, 0.0453 kg of ferrosilicon, 1.0547 kg of ferrovanadium, 1.0375 kg of ferrochrome, 0.523 kg of ferromanganese, and 0.01 kg of rare earth inoculant with a rare earth content of 10% (summarized in Table 3).

[0042] Table 3 Raw material usage in Example 1

[0043]

[0044] Charges are added into a medium frequency induction furnace for smelting in the order of scrap steel, pig iron, ferrochrome, ferromanganese, ferrovanadium, ferrosilicon and rare earth inoculant.

[0045] Melting step S2:

[0046] The power temperature of the medium frequency induction furnace was adjusted to 1550°C, the charge was refined for 30 minutes, and then kept warm for 30 minutes to obtain molten iron at 1550°C.

[0047] Step S3 of taking out of furnace and casting:

[0048] The molten iron at 1550°C is taken out of the furnace and poured into a preheated ladle as a melt. The melt is covered with dry exothermic powder, and the slag is removed while maintaining the temperature of the melt. Before taking out of the furnace, it is finally deoxidized with aluminum wire and poured into a plate-shaped resin sand mold for casting to obtain a wear-resistant alloy.

[0049] The advantages of wear-resistant alloys are described below through phase detection, metallographic analysis, hardness test and wear test. For the convenience of the test, the cast plate test block is cut into 50mm×50mm×4mm wear test pieces, and the wear test pieces are used as wear-resistant alloy samples for testing. The following are the test contents and results:

[0050] (1) Phase detection (SEM / EDS analysis)

[0051] The wear-resistant alloy samples were analyzed by scanning electron microscopy (JCM600, JEOL, Japan) and then phase detection (SEM / EDS analysis) was performed using an X-ray diffractometer (D-MAX-2500-PC, Japan). Figure 2 This is a diagram illustrating the results of SEM / EDS analysis.

[0052] See also Figure 2, from left to right, the distribution of element vanadium V, element chromium Cr, and rare earth element cerium Ce are shown respectively. The position distribution of the elements in the figure can be observed by comparing the long strip color plates at the bottom of the left, middle, and right figures (the color plates in the dotted boxes B1, B2, and B2 indicate the abundance of V, Cr, and Ce respectively). The bright part in the left figure indicates the distribution position of the element vanadium V, and the bright part in the right figure indicates the distribution position of the rare earth element cerium Ce. The two basically overlap. The distribution position of the element chromium Cr in the middle figure is very different from that of the element vanadium V in the left figure and the element cerium Ce in the right figure, indicating that the rare earth Ce mainly exists in the vanadium carbide VC phase. The distribution morphology of the element vanadium V is similar to a flower, with an approximately circular envelope surface, indicating that the vanadium carbide VC in the wear-resistant alloy tends to be spherical under the influence of rare earth Ce.

[0053] (2) Metallographic analysis

[0054] After rough grinding, fine grinding and polishing, the wear-resistant alloy samples were etched with aqua regia and photographed under an optical microscope (OM) (AxioImager, Zeiss, Germany). Five metallographic micrographs at 200 times magnification were taken continuously, and the best metallographic micrograph was taken for metallographic analysis. Figure 3 This is an illustration of metallographic analysis.

[0055] like Figure 3 As shown in the figure, the dark part b1 is the iron-based matrix of the wear-resistant alloy sample, which is mainly composed of austenite, indicating that the wear-resistant alloy has high toughness. Figure 3 The bright irregular shapes in the matrix are C1 carbon chromium compounds, which are evenly dispersed in the matrix. Figure 3 The medium-bright particles v1 are vanadium carbide VC, which are obviously larger spherical particles and are evenly dispersed in the matrix, indicating that the wear-resistant alloy has good wear resistance.

[0056] (3) Hardness test

[0057] According to the national standard GB / T230-91 "Metal Rockwell Hardness Test Method", the surface hardness of the wear-resistant alloy sample was tested on the HR-150A Rockwell hardness tester (the load was 150kg). After testing, the surface hardness of the wear-resistant alloy sample was 47.4HRC, indicating that the wear-resistant alloy has a high hardness.

[0058] (4) Wear test

[0059] Using a SUGA abrasive wear tester, 12×158mm 180-mesh silicon carbide sandpaper was fixed on the grinding wheel as the wear medium, and the test load was set to 19.6N. The wear-resistant alloy samples with a surface finish of 0.2μm Ra were subjected to three wear tests. The wear-resistant alloy samples before and after wear were microscopically observed and counted, and the average statistical result was taken.

[0060] The statistical results are as follows Figure 6 , Figure 7 As shown, that is, Figure 6 The left side of Figure 7 The black box line shows ( Figure 6 on the right side, Figure 7 The black triangle line shows the test results of the comparative examples in the following text, which will be described in detail later).

[0061] like Figure 6 As shown in the figure, after wear, the microhardness of the iron matrix of the wear-resistant alloy sample changes from 589HV to 774HV, an increase of 26%, indicating that considerable work hardening has occurred on the wear surface of the wear-resistant alloy. Figure 7 The wear amount of the wear-resistant alloy is inversely proportional to the hardness change, which means that the wear amount of the wear-resistant alloy sample is very small and the wear resistance is good.

[0062] The following describes Example 2 and Example 3: Example 2

[0063] The difference between Example 2 and Example 1 is that the element composition of the wear-resistant alloy is:

[0064] Carbon C: 2.3%, silicon Si: 1.0%, chromium Cr: 8.0%, manganese Mn: 5.0%, vanadium V: 6.0%, Ce: 0.2%, and the rest is iron Fe (summarized in Table 4).

[0065] Table 4 Composition of wear-resistant alloy in Example 2

[0066]

[0067] After calculation, the furnace materials required for refining 10 kg of wear-resistant alloy are 3.812 kg of scrap steel, 2.6 kg of pig iron, 0.0693 kg of ferrosilicon, 1.4766 kg of ferrovanadium, 1.383 kg of ferrochrome, 0.6596 kg of ferromanganese, and 0.02 kg of rare earth inoculant (summarized in Table 5), which has more alloy elements and rare earths than Example 1. The rest is the same as Example 1.

[0068] During smelting, the smelting temperature is 1520°C, smelting is performed for 50 minutes, and then the temperature is kept for 10 minutes. The temperature of the obtained molten iron is 1520°C. Compared with Example 1, the smelting temperature is reduced by 30°C and the holding time is reduced by 20 minutes. The rest is the same as Example 1.

[0069] Table 5 Raw material usage in Example 2

[0070]

[0071] Metallographic analysis shows that the wear-resistant alloy of Example 2 has a similar metallographic structure to that of Example 1, with the matrix being mainly austenite and having slightly more carbon-chromium compounds and spherical vanadium carbides VC than that of Example 1, indicating that its hardness and toughness are the same as those of Example 1, and has better wear resistance. Example 3

[0072] The difference between Example 3 and Example 1 is that the element composition of the wear-resistant alloy is:

[0073] Carbon C: 3%, silicon Si: 1.3%, chromium Cr: 10%, manganese Mn: 8%, vanadium V: 8%, Ce: 0.3%, and the rest is iron Fe (summarized in Table 6).

[0074] Table 6 Composition of wear-resistant alloy in Example 3

[0075]

[0076] After calculation, the furnace charge required for refining 10kg of wear-resistant alloy is 3.6kg of scrap steel, 1.7kg of pig iron, 0.111kg of ferrosilicon, 1.6876kg of ferrovanadium, 1.7292kg of ferrochrome, 1.1077kg of ferromanganese, 0.03kg of rare earth inoculant, and 0.08 of carburizer (summarized in Table 7). Compared with Example 2, it has more alloying elements and rare earths, and in order to make up for the carbon content, a carburizer is also added. The rest is the same as Example 1.

[0077] During smelting, the smelting temperature is 1500°C, the smelting time is 50 minutes, and then the temperature is kept at 20 minutes. The temperature of the obtained molten iron is 1500°C, the smelting time is relatively long, and the temperature keeping time is moderate. The rest is the same as Example 1.

[0078] Table 7 Raw material usage in Example 3

[0079]

[0080] Metallographic analysis shows that the wear-resistant alloy of Example 3 has a similar metallographic structure to that of Example 1, with the matrix being mainly austenite and having slightly more carbon-chromium compounds and spherical vanadium carbides VC, indicating that its hardness and toughness are the same as those of Example 1, and it has better wear resistance.

[0081] Summary of Examples

[0082] The mass percentages of the various alloying element components in the wear-resistant alloys listed in the above-mentioned Examples 1 and 3 correspond to the lower and upper limits of the content of the various alloying elements in the wear-resistant alloys, respectively, that is, the value range of the elemental composition of the wear-resistant alloy is: carbon C: 2.0% to 3.0%, silicon Si: 0.8% to 1.6%, chromium Cr: 6.0% to 12.0%, manganese Mn: 4.0% to 8.0%, vanadium V: 5.0 to 8.0%, rare earth element cerium Ce: 0.1% to 0.3%, and the rest is iron Fe, (summarized in Table 8)

[0083] Table 8 Composition of rare earth modified V-Cr-Mn iron-based wear-resistant alloy materials

[0084]

[0085] Relatively speaking, the alloy element content in Example 1 is relatively small, especially the amount of metallic vanadium is much smaller than that of general high-vanadium iron-based wear-resistant alloys, but it can still achieve or even exceed the wear-resistant effect of general high-vanadium wear-resistant alloys, and has the advantages of low refining cost, low refining temperature and simple process.

[0086] More alloying elements are used in Example 3. Although the cost is higher, more compounds that are beneficial to improving the properties of the alloy can be formed, and the alloy has higher wear resistance, hardness, and good toughness.

[0087] In Example 2, the sum of the mass percentages of the alloy elements except iron is 22.3%, which is close to 20%, and is a solution that takes into account both the production cost and performance of the wear-resistant alloy.

[0088] Comparative test

[0089] The beneficial effects of the wear-resistant alloy of Example 1 are illustrated below by comparing Comparative Example 1 and Comparative Example 2 with Example 1.

[0090] Comparative Example 1

[0091] The difference between Comparative Example 1 and Example 1 is that the raw materials do not include rare earth inoculant, and the rest are the same as Example 1.

[0092] A sample of the alloy (V-Cr-Mn iron-based alloy / 1550°C) prepared in Comparative Example 1 (hereinafter referred to as Comparative Sample 1) was subjected to metallographic analysis. The metallographic analysis results are shown in Figure 4 .

[0093] Figure 4 The enlarged morphology of vanadium carbide VC is shown. It can be seen that only the vanadium carbide VC at the edge of the figure forms irregular particles (part v21 in the figure), and most of the vanadium carbide VC in the middle is irregular petal-shaped (part v22 in the figure), and the distribution of vanadium carbide is uneven, and no similar Figure 3The spherical particles of vanadium carbide VC are uniformly distributed in the matrix, indicating that the V-Cr-Mn iron-based alloy prepared at a melting temperature of 1550°C and not containing the rare earth element cerium Ce is more prone to stress concentration and has worse wear resistance than Example 1.

[0094] Comparative Example 2

[0095] The difference between Comparative Example 1 and Example 1 is that the raw material does not include rare earth inoculant, the smelting temperature is increased to 1700° C., and the rest is the same as Example 1.

[0096] A sample of the alloy (V-Cr-Mn iron-based alloy / 1700°C) prepared in Comparative Example 2 (hereinafter referred to as Comparative Sample 2) was subjected to metallographic analysis. The metallographic analysis results are shown in Figure 5 .

[0097] like Figure 5 As shown, the dark part b3 is the matrix of the alloy, which is mainly austenite, and the bright irregular shape is the carbon chromium compound C3. Figure 3 The bright spot v3 in the matrix is ​​spheroidized granular vanadium carbide VC at high temperature, which is Figure 3 The number is significantly less and the volume is significantly smaller. The wear resistance is better than that of Comparative Example 1, but still worse than that of Example 1.

[0098] The sample of comparative example 2 was subjected to a wear resistance test, and the results are as follows: Figure 6 , Figure 7 shown.

[0099] like Figure 6 As shown in the figure, after wear, the microhardness of the iron-based matrix of the comparative sample 2 changes from 585HV to 719HV, which is 23% higher than that of the embodiment 1. Figure 7 The wear curve of the comparative sample 2 is also relatively flat. From the wear amount, the wear-resistant alloy of Example 1 is 15% less than that of the comparative sample 2. Therefore, the wear-resistant alloy sample of Example 1 has better wear resistance.

[0100] The following will introduce the functions of several elements used in the present invention:

[0101] Alloy elements play an extremely important role in metal materials. They affect both the organizational morphology of the materials and the properties of the materials themselves.

[0102] Carbon C is the most important element that determines the hardness and toughness of materials. It can improve hardenability and affect microstructure. In wear-resistant alloys, it has a medium-to-high carbon content (2-3%), so the material can cope with large impact loads and has the advantages of high hardness and high toughness. In addition, carbon can form carbides with other alloying elements (vanadium, chromium) in the material, giving the material certain special properties (see the description of the elements vanadium and chromium for details) and improving the wear resistance of wear-resistant alloys.

[0103] A small amount of silicon (Si) can significantly improve the yield limit and elastic limit of the material, and also improve the fatigue strength.

[0104] Chromium Cr and carbon can form different types of carbides, which can replace some iron atoms in cementite to form chromium-containing alloy cementite with higher microhardness (Fe,Cr)3C. When the chromium content in the material is high, complex carbides with higher microhardness (Cr,Fe)23C6 and (Cr,Fe)7C3 will be formed, so the wear-resistant alloy has high hardness. In addition, a higher chromium content can increase the size of the austenite area, which is beneficial to increase the toughness of the wear-resistant alloy. Chromium can also be dissolved in a small amount in austenite to improve the hardenability of the matrix.

[0105] Manganese Mn can expand the γ phase area of ​​the wear-resistant alloy and is an element that stabilizes austenite. When titanium and vanadium in the alloy form carbides that are insoluble in austenite, the hardenability of the material will be reduced. Adding manganese can change the adverse effects of these insoluble carbide elements and improve the hardenability of the material. At the same time, manganese Mn participates in the formation of Fe-Mn-C atomic groups, which can induce austenite to transform into martensite when the wear-resistant alloy is impacted, enhance the work hardening ability of the wear-resistant alloy, and improve the toughness of the wear-resistant alloy.

[0106] Vanadium V is a strong carbide-forming element. It combines with carbon to form vanadium carbide (VC) with very high microhardness. In wear-resistant alloys, vanadium carbide is in the form of nearly spherical particles, which is extremely beneficial to improving the wear resistance of the material.

[0107] Adding rare earth elements to wear-resistant alloys and undergoing modification can refine grains and strengthen grain boundaries. It can also improve the morphology of carbides, and deoxidize, desulfurize, and purify molten iron.

[0108] In the present invention, the rare earth element Ce can reduce the melting temperature of the wear-resistant alloy to about 1500° C. and can improve the morphology of vanadium carbide.

[0109] In the present invention, during smelting, the molten iron needs to be kept warm for 10 to 30 minutes, which is conducive to the full mixing and reaction of rare earth Ce and alloy elements, and is beneficial to the formation of granular vanadium carbide.

[0110] It should be noted that the above-mentioned embodiments illustrate rather than limit the invention and that those skilled in the art will be able to design alternative embodiments without departing from the scope of the appended claims.

[0111] In the claims, any reference signs placed between parentheses shall not be construed as limiting the claim.

Claims

1. Rare earth modified V-Cr-Mn iron-based wear-resistant alloy material, characterized in that: It is composed of the following components in percentage by mass: Carbon (C): 2.0% to 3.0%, Silicon (Si): 0.8% to 1.6%, Chromium (Cr): 6.0% to 12.0%, Manganese (Mn): 4.0% to 8.0%, Vanadium (V): 5.0% to 8.0%, Rare earth element Cerium (Ce): 0.1% to 0.3%, the rest is Iron (Fe), The rare earth modified V-Cr-Mn iron-based wear-resistant alloy material is made of raw materials meeting the above components, smelted at a specified smelting temperature of 1500-1550°C and a specified smelting time T1, and then kept warm for a specified holding time T2 to obtain molten iron at 1500-1550°C. The prescribed smelting time T1 is 30-50 min, the prescribed holding time T2 is 10-30 min, The raw materials include scrap steel, pig iron, ferrovanadium, ferrochrome, ferromanganese, ferrosilicon, and rare earth inoculants containing cerium.

2. The rare earth modified V-Cr-Mn iron-based wear-resistant alloy material according to claim 1, characterized in that: The raw materials also include a recarburizer.

3. The rare earth modified V-Cr-Mn iron-based wear-resistant alloy material according to claim 1 or 2, characterized in that: It is composed of the following components in percentage by mass: Carbon (C): 2.0%~2.3%, Silicon (Si): 0.80%~1.0%, Chromium (Cr): 6.0%~8.0%, Manganese (Mn): 4.0%~5.0%, Vanadium (V): 5.0~6.0%, Rare earth element Cerium (Ce): 0.1%~0.2%, and the rest is Iron (Fe).

4. A method for preparing a rare earth modified V-Cr-Mn iron-based wear-resistant alloy material, characterized in that: The wear-resistant alloy material is composed of the following components in percentage by mass: Carbon (C): 2.0% to 3.0%, Silicon (Si): 0.8% to 1.6%, Chromium (Cr): 6.0% to 12.0%, Manganese (Mn): 4.0% to 8.0%, Vanadium (V): 5.0% to 8.0%, Rare earth element Cerium (Ce): 0.1% to 0.3%, the rest is Iron (Fe), The preparation method comprises the following steps: Batching step S1: determining the element content of various raw materials, and calculating the mass of various raw materials for configuring the element components of the wear-resistant alloy material according to the determination results, and weighing the raw materials accordingly, wherein the raw materials include scrap steel, pig iron, ferrovanadium, ferrochrome, ferromanganese, ferrosilicon, and a rare earth inoculant containing cerium, Smelting step S2: putting the prepared raw materials into an electric furnace for smelting at a smelting temperature of 1500-1550°C and a specified smelting time T1, and then keeping the temperature for a specified holding time T2 to obtain molten iron at 1500-1550°C. Step S3 of taking out the furnace and casting: taking the molten iron at 1500-1550°C out of the furnace and pouring it into a preheated ladle as a melt, while maintaining the temperature of the melt and performing slag removal, and then pouring it into a mold for casting and forming to produce the rare earth modified V-Cr-Mn iron-based wear-resistant alloy material. The prescribed smelting time T1 is 30-50 min, and the prescribed insulation time T2 is 10-30 min.

5. The preparation method according to claim 4, characterized in that: The raw materials also include a recarburizer.

6. The preparation method according to claim 4 or 5, characterized in that: The wear-resistant alloy material is composed of the following components in percentage by mass: Carbon (C): 2.0%~2.3%, Silicon (Si): 0.80%~1.0%, Chromium (Cr): 6.0%~8.0%, Manganese (Mn): 4.0%~5.0%, Vanadium (V): 5.0~6.0%, Rare earth element Cerium (Ce): 0.1%~0.2%, and the rest is Iron (Fe).

Citation Information

Patent Citations

  • High-nitrogen, high-vanadium and high-chromium wear-resistant alloy and preparation method thereof

    CN113265580A

  • Wear resistant cast iron

    CN1798856A